2022
DOI: 10.1038/s41440-021-00839-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy and delivery of isometric resistance training as an adjunct therapy for blood pressure control: a modified Delphi study

Abstract: Uncontrolled hypertension remains the major risk factor for cardiovascular disease. Isometric resistance training (IRT) has been shown to be a useful nonpharmacological therapy for reducing blood pressure (BP); however, some exercise physiologists and other health professionals are uncertain of the efficacy and safety of IRT. Experts’ consensus was sought in light of the current variability of IRT use as an adjunct treatment for hypertension. An expert consensus-building analysis (Delphi study) was conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 94 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Considering that the contracting muscle mass is a crucial factor contributing to increases in BP and the subsequent compression of blood vessels, there are greater concerns regarding elevations in BP during exercises involving large muscle groups (such as squats and leg presses) compared with handgrip exercise. Aside from the wall squat, a recent modified Delphi study reported that handgrip and leg extension IET produce BP responses of > 30 mmHg sBP or 20 mmHg dBP, with smaller RPP increases compared with aerobic training [131]. Comparatively, a recent systematic review and meta-analysis [132] reported mean sBP responses of squat, leg extension and handgrip IET by + 46 mmHg, + 64 mmHg and + 33 mmHg.…”
Section: Safetymentioning
confidence: 99%
“…Considering that the contracting muscle mass is a crucial factor contributing to increases in BP and the subsequent compression of blood vessels, there are greater concerns regarding elevations in BP during exercises involving large muscle groups (such as squats and leg presses) compared with handgrip exercise. Aside from the wall squat, a recent modified Delphi study reported that handgrip and leg extension IET produce BP responses of > 30 mmHg sBP or 20 mmHg dBP, with smaller RPP increases compared with aerobic training [131]. Comparatively, a recent systematic review and meta-analysis [132] reported mean sBP responses of squat, leg extension and handgrip IET by + 46 mmHg, + 64 mmHg and + 33 mmHg.…”
Section: Safetymentioning
confidence: 99%
“…To gain expert consensus on a novel topic within sports science, the Delphi method has previously been utilized [ 25 29 ]. This method involves a panel of experts responding anonymously to a series of iterative questionnaires, with feedback from respondents used between rounds to reach a consensus within the group [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regular resistance training (RT) can also improve exercise performance and health ( 2 ). Appropriate RT prescriptions and strategies can effectively prevent and improve cardiovascular disease ( 3 ), diabetes ( 4 ), and arthritis ( 5 ), and can improve and delay the risk of sarcopenia and frailty-related diseases in the elderly ( 6 ). For athletes, improving muscle strength and mass through RT can help to develop increased explosive power and power output, and can improve muscle endurance to maintain exercise performance during competition ( 7 ).…”
Section: Introductionmentioning
confidence: 99%